Exploring stress coping strategies of frontline emergency health workers dealing Covid-19 in Pakistan: a qualitative inquiry - Munawar, Khadeeja; Choudhry, Riaz Fahad (Elsevier Inc. A, 2020)
Background The COVID-19 outbreak has gravely impacted the physical and psychological health of people. As the outbreak is ongoing, it is crucial to equip the emergency healthcare workers (HCWs) to be medically and psychologically prepared.